On the mutual relations of drill monitoring variables and the drill control system in tunneling operations. (February 2018) - Navarro, J.; Sanchidrian, J.A.; Segarra, P.; Castedo, R.; Paredes, C.; Lopez, L.M.
Highlights: The performance of the rig control system for jumbos with percussive-rotary drilling is studied. More than 65, 000 MWD signals for 11 different working conditions are used. Feed pressure is the parameter that governs the rig and the main one affected by variations in the rock mass. Rotation speed, water pressure and water flow are independent parameters and may also be affected by variations in the rock. The performance of the control system is independent of the rock type. The logging interval influences the delay response between parameters but not their mutual relation. A lower efficiency in terms of penetration rate is observed in manual drilling in comparison with semi-automatic drilling. Abstract: The mutual relation between Measurement While Drilling (MWD) parameters in percussive-rotary drilling is investigated in order to limit the number of MWD variables, and to select the more significant ones, that are required for a sound rock mass characterization. Cross-correlation of the MWD signals is used to determine their relations, the analysis of which brings a thorough understanding of the way that the rig control system governs the different parameters. Data recorded from six drilling machines, working in semi-automatic and manual mode, on three different rock types with different logging interval, have been analyzed. The results point out the feed pressure as the lead parameter that drives the adjustment of the other variables to optimize the drilling, thus being the upfront response to variations in the rock mass. Control parameters that limit this adjustment to minimize disturbances during the operation are also discussed. Finally, the influence of the rock mass condition on the MWD parameters response is studied.